A Development Design of Digital Story Conceptual Change-Oriented in Physics Subject - Yudi Kurniawan; Riski Muliyani (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
The result of need analysis shown that are difficulties still exist for teachers and students if they are learning in the new condition immediately. Therefore, this study aims to provide learning tools in the digital form and called as digital story conceptual change oriented (DSCC). This research was research and development by using ADDIE (analysis, design, development, implementation, and evaluation) design. This media tested the small scale test. The product designed on the subject of physics (Heat and Temperature) was validated by experts and tested on 147 respondents from Junior High School in West Singkawang and Central Singkawang sub-disctrict. The developed design was measured based on Learning Aspect (LA) which consists of: 1) Contextual problems, 2) Solution / Answer to the problem, 3) Communication effectiveness. The results of small-scale product trials shown that the Problem Solution aspect got the highest percentage of 93% and the communication aspect becomes the lowest with 73% while also having the worst responses with a percentage of 10%. This study could be references for researchers to improve the product to be better media and it could be so that it can be used directly and produce good learning outcomes.